Model Aksi Afirmatif Pemenuhan Hak Masyarakat Adat di Kawasan Ibu Kota Nusantara (IKN) - Haris Retno Susmiyati; Grizelda Grizelda; Wiwik Harjanti; Alfian Alfian; Aryo Subroto (Jurnal HAM, 2024)
The decision to build a new capital on the Kalimantan Island called Nusantara caused various conflicts, such as the neglect and marginalization of indigenous peoples and the ignoring of their certainty of access and meaningful participation. This paper explains how the substance of the Nusantara Capital development regulation is to provide full protection to Indigenous peoples or vice versa, how it impacts the protection of Indigenous people's rights, as well as how the affirmative action model fulfills the rights of Indigenous peoples in the Nusantara Capital area. Through a socio-legal approach as the method, the results of the study found that the constitution has regulated the recognition of indigenous peoples, but in the substance of regulations related to the Nusantara capital, the phrases that regulate are very weak. The phrases used do not explicitly ensure the protection of the rights of indigenous peoples, which has an impact on various neglect of the existence of indigenous peoples. As a result, a model of affirmative action is needed for indigenous peoples in the regulation of the Nusantara capital. This includes ensuring access for indigenous peoples to be involved in policymaking. Furthermore, transparency of information in the development of the Nusantara capital is important to formulate policies that accommodate the protection and fulfillment of the rights of indigenous peoples. It is important to ensure the recognition of indigenous peoples and their living space through an affirmative action model regulated by the head of the Nusantara capital authority.